CASE REPORT: PHYSIOTHERAPY TELESERVICE IN THE IMMEDIATE POSTOPERATIVE BREAST CANCER SURGERY - Trevisan, Lais de Abreu; Oliveira, Barbara Valente de; Salerno, Gisela Rosa Franco; Lima, Rafael de Albuquerque; Antonini, Marcelo (Mastology, 2026)
Introduction: Breast cancer is one of the most incidents and most common among women; surgical intervention is the main treatment, and physiotherapy plays an important role in the postoperative period, especially in the maintenance of range of motion and prevention/control of lymphedema. In the face of the contemporary scenario in which social isolation has been maintained due to the COVID-19 pandemic, the Federal Council of Physiotherapy and Occupational Therapy in Brazil released forms of remote care for patients who need clinical intervention. Objective: This study aims to report the experience of telecare in physiotherapy in the postoperative period of breast cancer surgery, focusing on aspects, pain, fatigue, mobility of the upper limb, and development of lymphedema. Case report: This is an experience report based on the telecare of a 61-year-old mastectomized patient, with 9 consultations, 8 in the remote format. The participant was evaluated regarding health habits, edema, sensation of pain, and tiredness using the Visual Scale of Pain (VAS), the Borg Rating of Perceived Exertion Scale, and a self-authored mastology questionnaire. In the initial evaluation, we found movement limitation (flexion-90º, extension-30º, and abduction-90º), the sensation of tightness in the scar, the sensation of a heavy limb, and dryness on the side of the surgery. In the final evaluation, we observed improvements when compared to the member opposed to surgery, in the gain of range of motion (flexion-180º, extension-45º, and abduction-180º), reduction of pain (VAS) and fatigue (BORG), and improvements in activities of daily living. Conclusion: The service in physical therapy was effective and obtained results similar to those expected in conventional face-to-face physical therapy treatments.